The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fmicb.2020.00831
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Among Expressed MicroRNAs and mRNAs in the Early Stages of Fowl Adenovirus Aerotype 4-Infected Leghorn Male Hepatocellular Cells

Abstract: Hydropericardium-hepatitis syndrome (HHS) is caused by some strains of fowl adenovirus serotype 4 (FAdV-4). However, the mechanism of FAdV-4 entry is not well understood. Therefore, to investigate the changes in host cellular response at the early stage of FAdV-4 infection, a conjoint analysis of miRNA-seq and mRNA-seq was utilized with leghorn male hepatocellular (LMH) cells at 30, 60, and 120 min after FAdV-4 infection. In total, we identified 785 differentially expressed (DE) miRNAs and 725 DE mRNAs in FAdV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…A recent study reported that gga-miR-148a-5p was significantly downregulated during avian leukosis virus subgroup J (ALV-J) infection and directly targeted PDPK1 to inhibit the proliferation and cell cycle of ALV-J-infected CEF cells [28]. Similarly, Wu et al demonstrated that the expression of gga-miR-148a-5p was suppressed in fowl adenovirus aerotype 4-infected hepatocellular cells [29]. Apparently in disagreement, our results showed that gga-miR-148a-5p was upregulated by APEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that gga-miR-148a-5p was significantly downregulated during avian leukosis virus subgroup J (ALV-J) infection and directly targeted PDPK1 to inhibit the proliferation and cell cycle of ALV-J-infected CEF cells [28]. Similarly, Wu et al demonstrated that the expression of gga-miR-148a-5p was suppressed in fowl adenovirus aerotype 4-infected hepatocellular cells [29]. Apparently in disagreement, our results showed that gga-miR-148a-5p was upregulated by APEC infection.…”
Section: Discussionmentioning
confidence: 99%
“…As a special class of regulatory factors in cells, miRNAs can regulate viral replication through different ways of action. FAdVcirc_013009 and FAdVcirc_011337 target the gga-miR-7475-5p, which negatively correlated with CREBZF and LFNG during FAdV-4 infection, and these genes were all associated with the host cell response to viral infection ( Wu et al, 2020 ). It is possible that viral circRNAs sequester functions from host miRNAs or viral miRNAs in order to regulate host or viral target genes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this technology, several studies have revealed that changes in cell gene transcription are an important aspect of the interaction between FAdV-4 and its host [ 38 , 40 , 41 ]. It is worth noting that our previous study showed that the binding and entry of FAdV-4 into LMH cells profoundly affect early cellular miRNA transcription profiles and that cellular miRNAs play an important role in FAdV-4 entry [ 39 ]. As another type of noncoding RNA, lncRNAs play an important regulatory role in the battle between virus and host, involving the transcription of viral genes, transcription of host genes, stability of mRNAs, translation of mRNAs and host antiviral response [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of these findings, lncRNAs are an emerging hotspot in host–virus interaction research. Recently, several studies have investigated the roles of transcription products in the interaction between FAdV-4 and its host [ 38 , 39 , 40 , 41 ] by transcriptome analysis. However, the function of cellular lncRNAs during FAdV-4 infection is poorly understood.…”
Section: Introductionmentioning
confidence: 99%